Microcellulose fibers-filled epoxy foams - Stefani, Pablo Marcelo (2008)
The dynamic‐mechanical behavior of epoxy foams reinforced with microcellulose fibers was investigated. Microcellulose fibers were obtained from sisal fibers by a several step process which includes chlorination, alkaline extraction, and bleaching. To analyze the effect of cellular structure on DMA properties, unreinforced and reinforced unfoamed epoxy samples were also used. SEM experiments demonstrated that the addition of microfiber modified the final morphology, decreasing the average cell size and increasing the number of cells per volume unit. The dynamic‐mechanical behavior of the reinforced samples, unfoamed epoxy and foamed epoxy, showed improvements with respect to the unreinforced ones, but the effect was remarkable in the second case.